Guinea Bissau Citizen Engagement : Mapping and NGOs Capacity Assessment Report - World Bank (World Bank, Washington, DC, 2020)
This report presents the findings of a rapid mapping and capacity assessment of nongovernmental organizations (NGOs) operating in Guinea Bissau. The assessment aimed to understand the role of NGOs in targeted service delivery sectors and in social mobilization. The findings of the assessment will inform proposed capacity building support that the World Bank plans to provide to NGOs in Guinea Bissau to strengthen their role in supporting Citizen Engagement (CE) approaches. Currently, NGOs and religious oriented institutions, including the Catholic church, play a crucial role in service provision in Guinea Bissau, including basic services such as health and education. As such, various internal and external stakeholders identify an outsized role for NGOs to play in supporting accountable and responsive service delivery. In this regard, the mapping and capacity assessment focused on development-oriented NGOs operating at the national and/or local levels. Nearly all of the NGOs that participated in this study were formally registered organizations that were development-oriented entities, which were not purely charitable, religious- and/or advocacy-oriented entities. The study explicitly excluded NGOs that were strictly humanitarian and did not engage in developmental work. Quantitative and qualitative research methods were used in the course of the data collection, including desk and media research, questionnaires, structured surveys, key informant interviews, and focus groups. Prior to field research, desk and media reviews were conducted to aggregate historical perspectives on civil society in Guinea Bissau and to identify gaps in analysis. Combined, these methodologies provided a variety of ways to crosscheck the self-reported data and perspectives of focus group participants with more structured survey and interview data.